Fates of Evolutionarily Distinct, Plastid‐type Glyceraldehyde 3‐phosphate Dehydrogenase Genes in Kareniacean Dinoflagellates. (15th March 2018) - Kamikawa, Ryoma; Yazaki, Euki; Tahara, Michiru; Sakura, Takaya; Matsuo, Eriko; Nagamune, Kisaburo; Hashimoto, Tetsuo; Inagaki, Yuji
Abstract: The ancestral kareniacean dinoflagellate has undergone tertiary endosymbiosis, in which the original plastid is replaced by a haptophyte endosymbiont. During this plastid replacement, the endosymbiont genes were most likely flowed into the host dinoflagellate genome (endosymbiotic gene transfer or EGT). Such EGT may have generated the redundancy of functionally homologous genes in the host genome—one has resided in the host genome prior to the haptophyte endosymbiosis, while the other transferred from the endosymbiont genome. However, it remains to be well understood how evolutionarily distinct but functionally homologous genes were dealt in the dinoflagellate genomes bearing haptophyte‐derived plastids. To model the gene evolution after EGT in plastid replacement, we here compared the characteristics of the two evolutionally distinct genes encoding plastid‐type glyceraldehyde 3‐phosphate dehydrogenase (GAPDH) in Karenia brevis and K. mikimotoi bearing haptophyte‐derived tertiary plastids: " gapC1h " acquired from the haptophyte endosymbiont and " gapC1p " inherited from the ancestral dinoflagellate. Our experiments consistently and clearly demonstrated that, in the two species examined, the principal plastid‐type GAPDH is encoded by gapC1h rather than gapC1p . We here propose an evolutionary scheme resolving the EGT‐derived redundancy of genes involved in plastid function and maintenance in the nuclear genomes of dinoflagellates that have undergone plastid replacements. Although K. brevis and K. mikimotoi are closely related to each other, the statuses of the two evolutionarily distinct gapC1 genes in the two Karenia species correspond to different steps in the proposed scheme.